Unsteady hydrodynamic forces acting on a hand and its flow field during sculling motion - Shimojo, H.; Sengoku, Y.; Miyoshi, T.; Tsubakimoto, S.; Takagi, H. (Human Movement Science, 2014)
The goal of this research is to clarify the mechanism by which unsteady forces are generated during sculling by a skilled swimmer and thereby to contribute to improving propulsive techniques. We used particle image velocimetry (PIV) to acquire data on the kinematics of the hand during sculling, such as fluid forces and flow field. By investigating the correlations between these data, we expected to find a new propulsion mechanism. The experiment was performed in a flow-controlled water channel. The participant executed sculling motions to remain at a fixed position despite constant water flow. PIV was used to visualize the flow-field cross-section in the plane of hand motion. Moreover, the fluid forces acting on the hand were estimated from pressure distribution measurements performed on the hand and simultaneous three-dimensional motion analysis. By executing the sculling motion, a skilled swimmer produces large unsteady fluid forces when the leading-edge vortex occurs on the dorsal side of the hand and wake capture occurs on the palm side. By using a new approach, we observed interesting unsteady fluid phenomena similar to those of flying insects. The study indicates that it is essential for swimmers to fully exploit vortices. A better understanding of these phenomena might lead to an improvement in sculling techniques.